2008
DOI: 10.1111/j.1365-2958.2008.06177.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation by the guanine nucleotide exchange factor Don1 is a main determinant of Cdc42 signalling specificity in Ustilago maydis

Abstract: SummaryThe highly conserved GTP-binding proteins Cdc42 and Rac1 regulate cytokinesis, establishment of cell polarity and vesicular trafficking. In the dimorphic fungus Ustilago maydis, Rac1 is required for cell polarity and budding, while Cdc42 is essential for cell separation during cytokinesis. The same cell separation defect is also observed in mutants that lack Don1, a guanine nucleotide exchange factor (GEF) of the Dbl family. We have generated a series of chimeric GTP-binding proteins consisting of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The change of fluorescence over time was used to assess mant-GDP incorporation into Rho4 in the presence and absence of the GEF. Similar conditions were also used in recent publications by Yeh et al (2007) and Hlubek et al (2008). The latter authors also used equal amounts of GEF and GTPase.…”
Section: Genetic Interaction Experimentsmentioning
confidence: 91%
“…The change of fluorescence over time was used to assess mant-GDP incorporation into Rho4 in the presence and absence of the GEF. Similar conditions were also used in recent publications by Yeh et al (2007) and Hlubek et al (2008). The latter authors also used equal amounts of GEF and GTPase.…”
Section: Genetic Interaction Experimentsmentioning
confidence: 91%
“…In addition, overexpression of Rho1 led to the reduction of filamentation. Overexpression of Rac1 triggers filamentation in U. maydis (13,29). We show here that deleting Rac1 eliminates the lethal effect imposed by either Rho1 or Pdc1 depletion.…”
mentioning
confidence: 83%
“…Cdc42, the yeast homolog of RacA, is a substrate of Cdc24 (24). In U. maydis, Don1 was identified as the GEF for Cdc42, and Cdc24 is proposed as the GEF for RacA to control the processes of cell septation and polarized growth, respectively (18,25,26). We previously showed that interaction of the GTP bound form of RacA with NoxR is essential for activation of the fungal Nox (13,16).…”
Section: Discussionmentioning
confidence: 99%